Correlation Between Mobile Phone Use Intensity with Carpal Tunnel Syndrome - Disha, Safira; Aida Fitri; Batubara, Chairil Amin; Surbakti, Khairul Putra (Sumatera Medical Journal, 2021)
Abstract. Background. High intensity of mobile phone use can cause Carpal Tunnel Syndrome. Repeated wrist positions and movements cause increase pressure in carpal tunnel, that condition can compress the median nerve. Objectives. To determine the correlation between mobile phone use intensity and Carpal Tunnel Syndrome in Medical Faculty North Sumatera University Student. Methods. This research used an observational analytic design with cross sectional method. The sample were 417 Medical Faculty North Sumatera University students who met the inclusion criteria and were not included in the exclusion criteria. The instrument of this research were Mobile Phone Use Questionnaire and Indonesian version of the Boston Carpal Tunnel Questionnaire. The research results were analyzed using the Statistical Package for Social Science application with the Rank Spearman Correlation Test. Results. Based on the Rank Spearman Correlation test, obtained p < 0,0001 which stated that there was a correlation between mobile phone use intensity with Carpal Tunnel Syndrome. The correlation coefficient of 0.177 indicated very weak correlation and correlation between two variables was unidirectional. Conclusion. There was correlation between mobile phone use intensity with Carpal Tunnel Syndrome in Medical Faculty North Sumatera University Student.